Towards a better understanding of odor removal from post-consumer plastic film waste A kinetic study on deodorization efficiencies with different washing media - Roosen, Martijn (Waste management (New York, N.Y.), 2021)
Copyright © 2020 Elsevier Ltd. All rights reserved.